Branding the Creative City of Design: Lesson from Singapore - Prayudi Prayudi; Kartika Ayu Ardhanariswari; Ninik Probosari (Jurnal Ilmu Komunikasi, 2022)
Over the last two decades, creative cities have become an issue of interest as governments in several countries have worked to develop ecosystems where the creative class can innovate and share ideas. Many city governments focus more on developing creative cities and pay less attention to their city's branding. This study aims to see Singapore as a newly appointed UNESCO creative city brand, even though it already has a destination brand. There are challenges about which brand should come first or how to strategically brand a city and ensure all interests are accommodated in the branding process. This study uses a qualitative method with in-depth interview data collection techniques with the Head of the Singapore Polytechnic Department of Architecture and Design, literature studies through books, journals, newspapers, and related matters, as well as observations in the city of Singapore. The results of this study show that Singapore's branding as a creative city of design is a component of the city-state's leading branding. First, the city branding process includes identifying the uniqueness of the city brand. In this case, the emphasis on Singapore is built and grown by design. Next is the development of a brand identity that differentiates Singapore from other UNESCO design creative cities. Finally, the delivery of brand messages to all relevant stakeholders. This research contributes to the development of branding concepts related to creative cities.